Amelioration of Salt Tolerance in Soybean (Glycine Max. L) by Plant-Growth Promoting Endophytic Bacteria Produce 1-Aminocyclopropane-1-Carboxylase Deaminase - Simarmata, Rumella; Ngadiman, Ngadiman; Rohman, Saifur; Simanjuntak, Partomuan (ANNALES BOGORIENSES, 2018)
Salinity is a major abiotic stress that can induce ethylene synthesis beyond the normal limits as plants response to stress and hence reduces crop productivity. The 1-aminocyclopropane-1-carboxylase deaminase (ACCD)-producing bacteria can reduce excessive ethylene synthesis by taking ACC (ethylene precursor) as a nitrogen source. This study showed the possibility of using endophytic bacteria in order to reduce the undesirable effects of salinity. Strain Pseudomonas putida PIR3C and Roultella terrigena PCM8 exhibited promising performance for promoting the growth of plant under salinity stress conditions. The results showed that bacterial inoculation was effective even in the presence of higher salinity levels. Strain P. putida PIR3C was the most efficient strain compared to the other strains and significantly increased shoot length, root length, dry weight, germination percentage, and reduced stem diameter. The role of ACCD in reducing ethylene production under salinity stress conditions was also studied by measuring the evolution of ethylene in vitro by soybean seeds treated with some ACCD bacterial strain. The maximum ethylene lowering capacity was observed in R. terrigena PCM8, the strain reduced ethylene production from 622.81 nmol.g-1(control) to 352.78 nmol.g-1 (43% reduction). The production of α-ketobutyrate, chlorophyll content and germination percentage from P. putida PIR3C was higher than other strains. The results suggested that strain P. putida PIR3C and R. terrigena PCM8 can be employed for salinity tolerance in soybean seedlings and may have better prospects for an amelioration of stress condition.